PENGARUH MODEL CHILDREN LEARNING IN SCIENCE (CLIS) TERHADAP HASIL BELAJAR DAN KETERAMPILAN KOLABORASI DALAM PEMBELAJARAN IPA DI SD: penelitian kuantitatif - gustari, anggita; Fatkhiyani, Kiki; Setiawardani, Wawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Natural Science is one of the subjects that has a close relationship with students' daily lives. In the process of learning science in the classroom, the main focus lies on experiments that link students' prior knowledge with the material to be learned. The purpose of this approach is to motivate students in learning as well as improve their learning outcomes and collaboration skills. This study aims to investigate the effect of the Children Learning In Science (CLIS) model on learning outcomes and collaboration skills of grade 4 students at UPTD SDN 1 Srengseng, Krangkeng District, Indramayu Regency. The method applied in this research is quantitative, with an experimental approach that produces data in the form of numbers. Data were collected through written tests and questionnaires. The results of the analysis showed an influence on student learning outcomes, which is reflected in the variable coefficient of 0.026, which is smaller than 0.05, in science learning using the CLIS model. Meanwhile, for the collaboration skills variable, the result shows 0.160 > 0.05, which indicates that there is no significant influence on collaboration skills. From the results of this study, it can be concluded that the Children Learning in Science (CLIS) model has a positive impact on students' learning outcomes in science, although it has no effect on their collaboration skills.